Bis(pentafluorophenyl)borane Induced Tandem Hydroboration‐Carboboration of Cyclooctatetraene. Issue 6 (1st February 2023) - Müller, Tizian; Hasenbeck, Max; Becker, Jonathan; Gellrich, Urs
Abstract: We report here the formation of the bridged boracycle 1 upon reaction of cyclooctatetraene with bis(pentafluorophenyl)borane. Computations indicate that the reaction commences with a hydroboration and that the high Lewis acidity of the bis(pentafluorophenyl)borane then induces a rearrangement with cleavage of a carbon–carbon bond via a nonclassical zwitterion and a final 1, 1‐carboboration. An intermediate of the reaction was captured as tri‐ tert ‐butylphosphine adduct. Abstract :